Ecologic control on the development of meridional ornamentation in the planktonic foraminiferal genus Rugoglobigerina (Late Cretaceous) and implications for taxonomy - F. Falzoni; M.R. Petrizzo; B. T. Huber; K. G. MacLeod (2013)
The wall ornamentation in Cretaceous planktonic foraminifera has been considered genetically controlled and taxonomically significant in analogy with Cenozoic taxa. For instance, the development of the meridional ornamentation is a diagnostic criterion used to discriminate the Late Cretaceous genera Costellagerina and Rugoglobigerina. Although some authors noted that the development of meridional ornamentation decreases poleward and could be ecologically controlled, this hypothesis was rejected for absence of evidence. Our study based on Rugoglobigerina specimens recovered at three mid-low latitude localities (Exmouth Plateau, Indian Ocean; Shatsky Rise, Pacific Ocean; Eratosthenes Seamount, Mediterranean Sea) confirms that the development of the meridional ornamentation is variable throughout the geographic and stratigraphic distribution of the genus. Stable isotope (δ13C and δ18O) analyses indicate that specimens showing a more developed meridional ornamentation always yield higher δ13C values than co-occurring less ornamented morphotypes and we interpret these data to indicate an ecologic/metabolic control regulating the development of the meridional ornamentation. Moreover, we highlight the difficulty in discriminating between Rugoglobigerina, Costellagerina and Archaeoglobigerina at mid-high latitudes, where species show identical shell morphology and ornamentation. Our study challenges the assumption that the external features of the wall represent reliable criteria for the taxonomic discrimination of Cretaceous planktonic foraminifera.